The influence of the environment on the implementation of good university governance in private universities in the city of Bandung - Eka Surachman; Heny Hendrayati; Meriza Hendri; Marchela Indah Atrisia; Noviana Riza (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Good university government is related to the entire system that is formed starting from rights, processes and control, both inside and outside company management. This research aims to investigate the influence of the external and internal environment on the application of the principles of Good University Governance (GUG) and their implications for the quality of private universities (PU) in Bandung City. This study uses a quantitative approach with a research instrument in the form of a questionnaire designed to measure perceptions of external and internal environmental conditions, implementation of GUG, competitive strategies, and quality of PU. Data analysis was carried out by carrying out normality tests, data linearity tests, and SEM assumptions. The research results show that the external and internal environment has a significant influence on the implementation of GUG at PU Bandung. The findings of this research confirm that the external and internal environment plays an important role in implementing GUG at PU Bandung. Furthermore, the implementation of GUG has a positive impact on the overall quality of PU. By implementing GUG principles well, private universities can strengthen their competitive strategies and overall improve their quality in society.